THE EFFECTS OF NPL, LDR, NIM, AND OER ON THE PROFITABILITY OF BANKS’ ACCORDING TO BANK GROUP BASED ON CORE CAPITAL - Hani, Ardelya Nastiti Laila; Moh. Athoillah (Contemporary Studies in Economic, Finance and Banking, 2024)
The purpose is to determine the effect of risks in the banking industry on bank’s profitability in KBMI. Panel data regression analysis is used to describe the effect between the independent variable on the dependent variable. The population itself is limited to five banks with the highest equity on every KBMI up to 2022 which is collected through their financial statement. NPL has a not significant negative in KBMI 1, KBMI 2, and KBMI 3. While in KBMI 4 and all KBMI has a not significant positive effect. LDR has a significant negative effect on KBMI 1, not significant positive on KBMI 2, and significant positive on KBMI 4. NIM has significant positive effect on KBMI 1, KBMI 3, and KBMI 4. While in KBMI 2 and all KBMI has a not significant positive object. BOPO has a negative significant effect on all KBMI.